Sex Differences in the Patterns of Systemic Agent use Among Patients With Psoriasis: A Retrospective Cohort Study in Quebec, Canada - Milan, Raymond; LeLorier, Jacques; Brouillette, Marie-Josée; Holbrook, Anne; Litvinov, Ivan V.; Rahme, Elham (Frontiers in Pharmacology, 2022)
Background: Sex differences exist in psoriasis manifestation and expectations from treatment with systemic agents, including, conventional systemic agents (CSA) and tumor necrosis factor inhibitors or ustekinumab (TNFi/UST). However, sex differences in patterns of systemic agent use, such as CSA discontinuation and switch from CSA to TNFi/UST have not been examined. Objectives: To assess sex differences in patterns of CSA use and identify factors associated with switch to (or add) a TNFi/UST and those associated with CSA discontinuation. Methods: We conducted a retrospective cohort study using the Quebec health administrative databases. We included patients with psoriasis initiating a CSA in 2002–2015. We excluded patients with a psoriasis diagnosis in the 3 years prior to the first diagnosis date between 2002 and 2015, and those with a systemic agent dispensation in the year prior to that date. We used Cox regression models with the Least Absolute Shrinkage and Selection Operator method to identify factors associated with Switch/add TNFi/UST, and those associated with CSA discontinuation. Separate analyses were performed for male and female patients. Results: We included 1,644 patients (55.7% females, mean age 60.3 years), among whom 60.4% discontinued their CSA and 7.4%, switched/added TNFi/UST (3.4% switched and 4.0% added) within a median of 0.78 years of follow-up. Among male and female patients, rates of Switch/add TNFi/UST per 1,000 person-year were 49.1 and 41.0 and rates of CSA discontinuation were 381.2 and 352.8. Clinical obesity in male patients (HR 3.53, 95% CI 1.20–10.35), and adjustment/somatoform/dissociative disorders (HR 3.17, 95% CI 1.28–7.85) and use of nonsteroidal anti-inflammatory drugs (HR 2.70, 95% CI 1.56–4.70) in female patients were associated with Switch/add TNFi/UST. Male patients followed by a rheumatologist (HR 0.66, 95% CI 0.46–0.94) and those with a prior hospitalization (HR 0.70, 95% CI 0.57–0.87) were at lower risk of CSA discontinuation, while those initiated on acitretin (vs methotrexate) were at higher risk to discontinue their CSA (HR 1.61, 95% CI 1.30–2.01). Female patients with rheumatoid arthritis comorbidity (HR 0.69, 95% CI 0.51–0.93), those with a dispensed lipid-lowering agent (HR 0.72, 95% CI 0.59–0.88) and hypoglycemic agent (HR 0.75, 95% CI 0.57–0.98) and those initiated on methotrexate (vs all other CSAs) were less likely to discontinue their CSA. Male and female patients entering the cohort between 2011 and 2015 were at reduced risk of CSA discontinuation compared to those entering the cohort before 2011. Conclusion: Most male and female patients discontinued their CSA within 1 year of follow-up. Our study highlighted sex differences in patients’ characteristics associated with switch/add a TNFi/UST and CSA discontinuation; treatment switch and discontinuation may be indications of treatment failure in most patients.